Pharmacokinetic Analysis of Piperacillin Administered with Tazobactam in Critically Ill, Morbidly Obese Surgical Patients. Issue 1 (17th July 2013) - Sturm, Ashley W.; Allen, Nichole; Rafferty, Kelly D.; Fish, Douglas N.; Toschlog, Eric; Newell, Mark; Waibel, Brett
<x xml:space="preserve">Abstract</x> Study Objective To evaluate the steady‐state pharmacokinetic and pharmacodynamic parameters of piperacillin in morbidly obese, surgical intensive care patients. Design Open‐label single‐center prospective study. Setting Level I trauma center and university‐affiliated teaching institution. Patients Nine morbidly obese (body mass index [BMI] 40.0 kg/m2 or higher) hospitalized patients admitted to the trauma and surgical intensive care service who were treated with piperacillin‐tazobactam between December 15, 2010, and April 18, 2012. Intervention Patients received intravenous piperacillin‐tazobactam 4.5 g every 6 hours, administered as a 30‐minute infusion. Measurements and Main Results Patients' blood samples were collected after the administration of the fourth, fifth, or sixth dose (i.e., at steady state). Serum piperacillin concentrations were determined by using a validated high‐performance liquid chromatography assay; these concentrations were used to estimate pharmacokinetic parameters, and 5000‐patient Monte Carlo simulations were performed. The probability of target attainment for 50% or higher of the dosing interval during which free (unbound) drug concentrations exceeded the minimum inhibitory concentration (%fT > MIC) of likely pathogens was calculated for piperacillin at various MICs. Patient demographic and clinical characteristics included a mean ± SD total body weight of 164 ± 50 kg, BMI of 57 ± 15.3 kg/m2, and age 57 ± 11 years, and a median Acute Physiology and Chronic Health Evaluation II score of 22 (interquartile range 21–26). Compared with values previously reported in other populations, the volume of distribution was increased in the study patients, and total system clearance was decreased. The net result was a mean ± SD half‐life of 3.7 ± 1.2 hours compared with ~1 hour reported in other populations. This contributed to an extended %fT > MIC for likely pathogens. Results from all nine patients showed %fT > MIC of 100% at the susceptibility breakpoint MIC of 16 mg/L and 85% or higher at an MIC of 32 mg/L. Conclusion The pharmacokinetics of piperacillin is altered in morbidly obese, surgical intensive care patients. The use of standard‐dosage piperacillin‐tazobactam 4.5 g intravenously every 6 hours was shown to be an appropriate dosage for this study population.